Charles-Marie Widor: symphonies 3 & 8 - Widor, Charles-Marie 1844-1937; Lehtola, Jan (Finland Alba records, 2009)
CHARLES-MARIE WIDOR: SYMPHONIES 3 & 8. Jan Lehtola, organist. Organ of the church of Saint-François-deSales, Lyon, France (III/56 Cavaillé-Coll, 1880; restored by Merklin & Kuhn, 1964). Alba Records Oy ABCD 306 (SACD). Alba.fi/kauppa/levykatalogi/7. Charles-Marie Widor had a special connection to the church and organ of Saint-François-deSales in Lyon. Widor's father, François-Charles, was organist there when Charles-Marie was a boy. The church's original organ by Callinet-Rouffach, built in 1838, was designed in part by Charles-Marie's grandfather Jean. At age eleven, Charles-Marie deputized for his father as organist at the church. The young Widor's close association with Cavaillé-Coll is well known; Widor designed modifications to the Lyon organ according to Cavaillé-Coll's thennovel tonal innovations in the symphonic style. The famed builder ultimately replaced the instrument with a new one in 1880, upon which Widor performed the inaugural recital, which included his Fifth Symphony. This instrument, following some restorative work in 1964, retains its original disposition. Thus, it joins the organ of Saint-Sulpice and only a few others as an unaltered specimen of the master-builder's work. While the organ of Saint-Sulpice is his largest, and that of Rouen is feted for its great power, the relatively modest instrument at Saint-François-de-Sales is distinguished for its poetic beauty and expressiveness, inherent particularly in the lovely solo voices and soft combinations.